Comparison Study of Two Differently Clicked 18F-Folates-Lipophilicity Plays a Key Role - Kathrin Kettenbach; Laura M. Reffert; Hanno Schieferstein; Stefanie Pektor; Raphael Eckert; Matthias Miederer; Frank Rösch; Tobias L. Ross (MDPI AG, 2018)
Within the last decade, several folate-based radiopharmaceuticals for Single Photon Emission Computed Tomography (SPECT) and Positron Emission Tomography (PET) have been evaluated; however, there is still a lack of suitable 18F-folates for clinical PET imaging. Herein, we report the synthesis and evaluation of two novel 18F-folates employing strain-promoted and copper-catalyzed click chemistry. Furthermore, the influence of both click-methods on lipophilicity and pharmacokinetics of the 18F-folates was investigated. 18F-Ala-folate and 18F-DBCO-folate were both stable in human serum albumin. In vitro studies proved their high affinity to the folate receptor (FR). The lipophilic character of the strain-promoted clicked 18F-DBCO-folate (logD = 0.6) contributed to a higher non-specific binding in cell internalization studies. In the following in vivo PET imaging studies, FR-positive tumors could not be visualized in a maximum intensity projection images. Compared with 18F-DBCO-folate, 18F-Ala-folate (logD = −1.4), synthesized by the copper-catalyzed click reaction, exhibited reduced lipophilicity, and as a result an improved in vivo performance and a clear-cut visualization of FR-positive tumors. In view of high radiochemical yield, radiochemical purity and favorable pharmacokinetics, 18F-Ala-folate is expected to be a promising candidate for FR-PET imaging.